2021
DOI: 10.1192/j.eurpsy.2021.6
|View full text |Cite
|
Sign up to set email alerts
|

The association between C-reactive protein, mood disorder, and cognitive function in UK Biobank

Abstract: Background Systemic inflammation has been linked with mood disorder and cognitive impairment. The extent of this relationship remains uncertain, with the effects of serum inflammatory biomarkers compared to genetic predisposition toward inflammation yet to be clearly established. Methods We investigated the magnitude of associations between C-reactive protein (CRP) measures, lifetime history of bipolar disorder or major depression, and cognitive function (reaction time and visuospatial m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 37 publications
1
26
0
Order By: Relevance
“…The primary outcome variable was inflammation as measured by high-sensitivity C-reactive protein (CRP) collected via blood samples during the baseline data collection ( Fry et al., 2019 ; Milton et al., 2021 ). Circulating CRP levels were measured using high sensitivity assays of all participants at baseline.…”
Section: Methodsmentioning
confidence: 99%
“…The primary outcome variable was inflammation as measured by high-sensitivity C-reactive protein (CRP) collected via blood samples during the baseline data collection ( Fry et al., 2019 ; Milton et al., 2021 ). Circulating CRP levels were measured using high sensitivity assays of all participants at baseline.…”
Section: Methodsmentioning
confidence: 99%
“…The COVID-19 pandemic also provides an excellent example of the power of embedding a highly simplified, randomized trial platform comparing available and licensed medicines in real world settings. The RECOVERY trial was rapidly designed and set up in March 2020 5 . It randomized over 35,000 patients by February 2021.…”
Section: Learning From the Global Response To Covid-19 To Accelerate Innovation In Mental Health Trialsmentioning
confidence: 99%
“…In a population-representative cross-sectional analysis of >40,000 adults, a higher CRP level was associated with poorer executive functioning, which was especially true in the presence of depression and even existed in early adulthood 4 . Longitudinally, high levels of inflammatory markers have been linked to long-term cognitive decline, involving deterioration of memory and executive function 5 . A proteome-wide association study of older-adult brain donors indicated increased inflammation in brains of cognitively impaired persons as compared to those of cognitive stable persons 6 .…”
mentioning
confidence: 99%
“…While inflammation is an essential component of immunosurveillance and host defense, a chronic low-grade inflammatory state is a pathological feature of a wide range of chronic health conditions that is also known to affect brain and psychological development 9,10 . Second, we examined genetic profiles of inflammation (i.e., polygenic scores of CRP, PGS-CRP 11 ), because there are genetic correlations of CRP with mood disorders in adults, such as PTSD 12 and depressive symptoms 13 that may include causal effects of CRP on depression 14,15 . Third, we previously reported that socioeconomic disadvantage and Latinx compared to White identity is associated with the pace of multi-system biological aging, as indicated by DunedinPoAm 16 , in an earlier sub-sample of salivary DNA-methylation data from the Texas Twin Project (N=600) 17 .…”
Section: Textmentioning
confidence: 99%